Arsenic residues in broiler meat and excreta at arsenic prone areas of Bangladesh - Ghosh, Amalendu; Awal, Md. Abdul; Majumder, Shankar; Sikder, Mahmudul Hasan; Rao, Damanna Ramkishan (Bangladesh Journal of Pharmacology, 2012)
The aims of this study were to detect arsenic concentrations in feed, drinking water, tissues and excreta of broiler chickens in Bangladesh; and to assess the effect of arsenic in feed and drinking water on the retention of arsenic in broiler tissues and excreta. Total arsenic concentration (inorganic plus organic) was determined by atomic absorption spectrophotometer. Mean (± SE) levels of arsenic in drinking water, feed (dry weight) and excreta (dry weight) were 80.4 ± 5.5 µg/L, 119.0 ± 4.7 µg/kg and 1221.8 ± 58.3 µg/kg, respectively. In tissues (wet weight), highest arsenic concentration (µg/kg) was in skin (218.8 ± 11.7), followed by liver (102.1 ± 8.0), lung (96.3 ± 5.6), kidney (88.2 ± 7.5) and thigh muscle (67.8 ± 5.1). Arsenic in broiler meat was below the maximum tolerable limits for humans. Accumulations of arsenic in tissues and excreta were boosted with the relative increment of arsenic in drinking water and feed. High arsenic in excreta could be an environmental issue in Bangladesh.